3-[(1-Benzyl-1H-1,2,3-triazol-4-yl)methyl]-1,5-dimethyl-1,5-benzodiaze pine-2,4-dione - Dardouri, R.; Rodi, Y.K.; Saffon, N.; Essassi, E.M.; Ng, S.W. (International Union of Crystallography, 2010)
The title compound, C21H21N5O2, is a 1,4-dimethyl-1,2,3-triazole having dimethylbenzodiazepindione and phenyl substituents on each methyl group; the substituents are positioned on opposite sides of the five-membered ring. The seven-membered fused-ring of the larger substituent adopts a boat-shaped conformation (with the methine C atom as the prow).